Oralidad, lectura y escritura competencias mediadoras del aprendizaje del currículo de Química: el caso del equilibrio químico - Candela, Boris Fernando (Revista Científica, 2020)
The researchers of the education in chemistry have considered that one of the key goals of the curriculum of this discipline, is the scientific literacy in the fundamental sense (to speak, to read and to write) and derivative (to understand the products and process of chemistry). Although, this purpose has been a key element of the current curricular reforms of this discipline, in the teaching practice it has been difficult to achieve; given that teachers have focused on assisting students in the understanding of theoretical models, neglecting the development of linguistic competences of orality, reading and writing as constitutive elements of chemistry. A qualitative methodology was used for case studies, which required the collection of data from documentary sources such as: videos, field notes, narrative stories and student work. The results allowed us to see that to achieve the desired literacy in the chemistry classroom, the teacher is required to consciously assist his students in the integrated development of the speaking, reading and writing language skills of and about chemistry, within a sociocultural context.